(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents analyzes of the results of studies on the distribution of Inula glauca C.Winkl., Inula grandis Schrenk ex Fisch. & C.A.Mey., Inula helenium L, Inula macrolepis Bunge, Inula rhizocephala Schrenk ex Fisch. & C.A.Mey., Inula rhizocephala Schrenk ex Fisch. & C.A.Mey., which are representatives of the Inula L. genus distributed in Central Asia, by ecoregions.